2017
DOI: 10.1111/phpp.12299
|View full text |Cite
|
Sign up to set email alerts
|

Does imiquimod pretreatment optimize 308‐nm excimer laser (UVB) therapy in psoriasis patients?

Abstract: Psoriasis continues to be a debilitating skin disease affecting 1-3% of the United States population. Although the effectiveness of several current biologic therapies have described this pathology as a IL-23, TNF-α and Th17-mediated disease, less invasive approaches are still in use and in need of refinement. One of these is the usage of narrow band-UVB (NB-UVB) therapy to deplete specifically intra-epidermal CD3+, CD4+ and CD8+ cells to clear psoriatic plaques. In order to improve NB-UVB therapy, we sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…First, the Q-switched Nd:YAG laser in which ultraviolet 353 nm laser irradiation is changed from 1064 nm (infrared) wavelength using a special crystal. The second type is a gas (excimer) laser, commonly used in the treatment of psoriasis [ 22 , 23 ]. The third type is a metal vapor laser [ 24 ].…”
Section: The Uv Light (10–400 Nm)mentioning
confidence: 99%
“…First, the Q-switched Nd:YAG laser in which ultraviolet 353 nm laser irradiation is changed from 1064 nm (infrared) wavelength using a special crystal. The second type is a gas (excimer) laser, commonly used in the treatment of psoriasis [ 22 , 23 ]. The third type is a metal vapor laser [ 24 ].…”
Section: The Uv Light (10–400 Nm)mentioning
confidence: 99%
“…In previous studies, GRAMD1A was found to accumulate at autophagosome initiation sites, influence cholesterol distribution during starvation, and participate in autophagosome biogenesis [ 24 ]. Besides, as one of the genes in the TLR7 regulatory pathway, GRAMD1A can be used to assess the response of psoriasis after treatment [ 25 ]. In human cancers, GRAMD1A is currently only found to promote proliferation, migration, and invasion of hepatocellular carcinoma as well as the expansion of hepatocellular carcinoma stem cells [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%